2015
DOI: 10.3389/fnins.2015.00391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alternating current stimulation on the healthy and diseased brain

Abstract: Cognitive and neurological dysfunctions can severely impact a patient's daily activities. In addition to medical treatment, non-invasive transcranial alternating current stimulation (tACS) has been proposed as a therapeutic technique to improve the functional state of the brain. Although during the last years tACS was applied in numerous studies to improve motor, somatosensory, visual and higher order cognitive functions, our knowledge is still limited regarding the mechanisms as to which type of ACS can affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 95 publications
(228 reference statements)
1
33
0
Order By: Relevance
“…The waveform of the stimulation changes cyclically over time, with either sinus pulses or square pulses that penetrate the skull through the electrodes placed over the surface of the scalp or are transmitted through the eye and optic nerve to the brain (19, 20). The effects of tACS at the neuronal level highly depend on the parameters used, i.e., current density, frequency range, electrode size, and the location of the stimulation electrode (21). Most of the applied stimulation frequencies are within the human EEG frequency range inducing local oscillatory activity in a stimulated brain area (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The waveform of the stimulation changes cyclically over time, with either sinus pulses or square pulses that penetrate the skull through the electrodes placed over the surface of the scalp or are transmitted through the eye and optic nerve to the brain (19, 20). The effects of tACS at the neuronal level highly depend on the parameters used, i.e., current density, frequency range, electrode size, and the location of the stimulation electrode (21). Most of the applied stimulation frequencies are within the human EEG frequency range inducing local oscillatory activity in a stimulated brain area (22).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the applied stimulation frequencies are within the human EEG frequency range inducing local oscillatory activity in a stimulated brain area (22). In tACS, a frequency that matches the endogenous frequency could entrain network oscillations, and in our tACS protocol, we used 3 Hz similar to the frequency of the spike-slow waves of our patient (21). This effect is known as phase-locked waves (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been shown that cranial AC stimulation may alter EEG pattern towards a more relaxed state, however the effects are dependent on the parameters of the specific stimulation (Paulus 2011). Several studies investigated the effects of AC on perception, memory, motor and cognitive function, as well as on mechanisms for cognitive control (Van Driel et al 2015, Hamid et al 2015, Antal & Paulus 2013. The obtained findings were heterogeneous and dependent on the frequencies and other experimental parameters used.…”
Section: Transcranial Alternating Current Stimulation (Tacs) and Tranmentioning
confidence: 99%
“…Because tACS is a highly flexible technique in terms of frequency and montage, it boasts a series of successes across a range of topics (for reviews, see Abd Hamid et al, 2015;Veniero et al, 2016;Vosskuhl et al, 2018). Higher cognitive functions such as memory (working memory, Polanía et al, 2012;Hoy et al, 2015;Alekseichuk et al, 2016Alekseichuk et al, , 2017Chander et al, 2016;Tseng et al, 2016Tseng et al, , 2018Violante et al, 2017;Hu et al, 2018;short-term memory, Vosskuhl et al, 2015; memory consolidation, Marshall et al, 2006;Lustenberger et al, 2016), fluid intelligence (Santarnecchi et al, 2013(Santarnecchi et al, , 2016, creativity (Lustenberger et al, 2015), risk taking (Sela et al, 2012;Wischnewski et al, 2016), and decision making (Polanía et al, 2015) have all been successfully modulated by tACS; as have emotion processing (Janik et al, 2015), voluntary movement (Pogosyan et al, 2009;Joundi et al, 2012;Heise et al, 2017), speech perception (Rufener et al, 2016a,b;Wilsch et al, 2018), mental rotation (Kasten and Herrmann, 2017;Kasten et al, 2018a), vision (Helfrich et al, 2014a(Helfrich et al, ,b, 2016aKar and Krekelberg, 2014;Strüber et al, 2014;Cecere et al, 2015;Minami and Amano, 2017;Herring et al, 2...…”
Section: Transcranial Alternating Current Stimulationmentioning
confidence: 99%